2020
DOI: 10.1002/ppul.24724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure rise time on ventilator parameters and gas exchange during neonatal ventilation

Abstract: Background Pressure rise time (PRT), also known as slope time to the peak inflating pressure can be set on some modern neonatal ventilators. On other ventilators, PRT is determined by the set circuit flow. Changing slope time can affect mean airway pressure (MAP), oxygenation, and carbon dioxide elimination. Our aim was to investigate the effect of PRT on ventilator parameters and gas exchange during volume‐guaranteed ventilation. Methods In a crossover study, 12 infants weighing greater than 2 kg were ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, the respiratory mechanics-related parameters improved, which is consistent with previous reports [ 24 , 27 ]. As reported by Chong et al, the respiratory parameters did not improve significantly although some of the ventilation parameters did improve significantly [ 23 ]. Mechanical ventilation increased the expression of NLRP3 mRNA in alveolar macrophages and caused lung inflammation dependent on NLRP3 inflammatory bodies [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, the respiratory mechanics-related parameters improved, which is consistent with previous reports [ 24 , 27 ]. As reported by Chong et al, the respiratory parameters did not improve significantly although some of the ventilation parameters did improve significantly [ 23 ]. Mechanical ventilation increased the expression of NLRP3 mRNA in alveolar macrophages and caused lung inflammation dependent on NLRP3 inflammatory bodies [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 73%
“…When using the Ingmar ASL5000 in a study to create a passive two-compartment lung model, increasing the IRT helps to balance inspiratory pressure, chamber-specific tidal volume, and volume equilibrium [ 22 ]. A study involving 12 infants weighing over 2 kg indicated that varying IRTs during synchronized intermittent positive pressure ventilation or PCV-VG impacted specific ventilation parameters but did not significantly affect oxygenation and carbon dioxide output [ 23 ]. Extending the duration of time spent inhaling helped sustain the rise in alveolar pressure, decrease the dead space, enhance arterial oxygen levels and respiratory performance, optimize gas exchange and arterial oxygen levels, and lower the airway pressure [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of different PRTs in neonatal ventilation is uncertain. 20 We have also found that a significant proportion of ventilator inflations during AC-VG ventilation contain periods of inspiratory hold or contains no expiratory hold, the occurrence and significance of which in neonates are not known as there are few studies analysing short periods. 21 Ventiliser allows for quantitative analysis of inflations over long periods and will facilitate such studies in future.…”
Section: Discussionmentioning
confidence: 93%